Assessment of Critical Knowledge on Maternal and Newborn care Services among Primary Level Nurse Mid-wives in Kapilvastu District of Nepal - Acharya, D.; Paudel, R. (Kathmandu University Medical Journal, 2017)
Background Despite greater emphasis on maternal and neonatal health through policy and programming in Nepal, maternal and neonatal health is still not impressive. Health care providers’ knowledge assessment on maternal and neonatal care has been well documented elsewhere, but it is very little understood in Nepal. Objective The primary objective of this study was to assess the critical knowledge of primary level nurse- midwives on maternal and newborn care in Kapilvastu District of Nepal. Method This was an Institution based cross-sectional study, conducted in Kapilvastu district, Nepal among sixty eight nurse-midwives. The participants were selected using simple random sampling technique. For collecting the data, health institutions were visited by enumerators for a month from 1st October to 1st November 2012. Data were entered into Microsoft Excel, cleaned and analyzed using SPSS version 17.0. Result More than 3/4th of the nurse-midwives had 10-20 years of experience. Majority of them (89.7%) had poor knowledge in taking action to prevent mother to child transmission for HIV positive women. More than half of them (54.4%) had some knowledge in performing the active management of third stage of labor whereas almost half (51.5%) had poor knowledge to actions needed on post-partum haemorrhage (PPH). Similarly, more than two third (69.1%) had poor knowledge in newborn care. Conclusion Majority of the nurse-midwives were found to have either poor or some level of knowledge in most of the components of maternal and newborn care services. So, greater emphasis should be given to upgrade the knowledge of nurse mid-wives.